Associations of Smokeless Tobacco Use With Cardiovascular Disease Risk: Insights From the Population Assessment of Tobacco and Health Study. Issue 7 (6th January 2022) - Rezk-Hanna, Mary; Warda, Umme Shefa; Stokes, Andrew C; Fetterman, Jessica; Li, Jian; Macey, Paul M; Darawad, Muhammad; Song, Yeonsu; Ben Taleb, Ziyad; Brecht, Mary-Lynn; Benowitz, Neal L
Abstract: Introduction: Cigarette smoking is strongly associated with the development of cardiovascular disease (CVD). However, evidence is limited as to whether smokeless tobacco (ST) use is associated with CVD. Aims and Methods: Using data from 4347 adults in the Population Assessment of Tobacco and Health Study (2013–2014), we compared geometric mean concentrations of CVD-related harm biomarkers and biomarkers of exposure among exclusive ST users and exclusive cigarette smokers—in relation to recent nicotine exposure—and never tobacco users, adjusting for age, sex, race/ethnicity, income, body mass index, and CVD. Biomarker levels among exclusive ST users who were former established cigarette smokers were compared with exclusive cigarette smokers. Results: Compared with cigarette smokers, ST users had significantly higher concentrations of total nicotine equivalents (TNE) but lower concentrations of inflammatory (high-sensitivity C-reactive protein, interleukin-6, intercellular adhesion molecule, fibrinogen) and oxidative stress (8-isoprostane) biomarkers (all p < .05). Biomarker levels among ST users were similar to never smokers. ST users who were former cigarette smokers had lower levels of inflammatory and oxidative stress biomarkers and biomarkers of exposure (cadmium, lead, 1-hydroxypyrene, acrylonitrile, and acrolein), compared with cigarettes smokers ( p < .05), despite having higher TNE levels ( p < .05). Among cigarette smokers, but not among ST users, inflammatory biomarkers and TNE were highly correlated. Conclusions: ST use is not associated with increases in biomarkers of CVD-related harm and exposure, compared with never smokers, despite exposure to nicotine at levels higher than those observed among cigarette smokers. These findings support the concept that increases in CVD risk among cigarette smokers is caused primarily by constituents of tobacco smoke other than nicotine. Implications: Despite having higher levels of nicotine and compared with exclusive cigarette smokers, exclusive ST users (including those who were former cigarette smokers) had significantly lower concentrations of inflammatory and oxidative stress biomarkers, comparable to levels observed among never tobacco users. These findings suggest that increases in CVD risk among cigarette smokers is caused primarily by tobacco constituents other than nicotine and that switching to ST is likely associated with lower CVD risk.